2017
DOI: 10.1002/nau.23211
|View full text |Cite
|
Sign up to set email alerts
|

Role of intrinsic sphincter deficiency with and without urethral hypomobility on the outcome of tape insertion

Abstract: The reduced cure rate for ISD patients was due to the subgroup with a hypomobile urethra. A prospective study is needed to confirm that slightly shorter tape-urethra distances and a relative tape position more toward the mid-urethra will lead to better outcomes for this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…Several sonographic approaches have been used for the study of urogynecologic symptoms: suprapubic, translabial, transvaginal, transperineal, introital, 2D, 3D and 4D [1,13,19]. There is no consensus on optimal approach to be used for different situations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several sonographic approaches have been used for the study of urogynecologic symptoms: suprapubic, translabial, transvaginal, transperineal, introital, 2D, 3D and 4D [1,13,19]. There is no consensus on optimal approach to be used for different situations.…”
Section: Discussionmentioning
confidence: 99%
“…Also, no comparison was performed between different approaches [1]. PFS-TV is one of the methods recently applied to urogynecology [17][18][19]. Recent clinical studies on PFS-TV have confirmed the adverse effect of the CI point hypomobility on SUI cure rate after implantation of suburethral tape [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations